Psychosocial Support and Holistic Interventions for Indonesian Teen Mothers : Dukungan Psikososial dan Intervensi Holistik untuk Ibu Remaja - Alifia, Nazhwa; Azizah, Nurul (Wadah Inovasi Indonesia, 2025)
This study addresses the psychological and social challenges faced by Mrs. A, a 17-year-old Indonesian teenager, following an early marriage precipitated by an out-of-wedlock pregnancy. With high rates of teenage pregnancies being a significant issue in Indonesia, this case underscores the urgent need for comprehensive support from governments, institutions, and parents. Mrs. A's psychological distress, compounded by insufficient support from her husband and his family, highlights a critical knowledge gap in addressing young mothers' mental health needs. The research aims to evaluate the effectiveness of counseling and personal approaches, including teaching acupressure massage at Li4 and LR3 points to reduce anxiety. Results indicate that targeted psychological interventions and holistic support systems are crucial for optimizing midwifery care and improving outcomes for teenage mothers. These findings suggest that a multi-faceted support approach is essential for addressing the complex needs of young mothers in similar contexts.